Politicized trade: What drives withdrawal of trade preferences? - Martin Gassebner; Arevik Gnutzmann-Mkrtchyan (ETH Zurich, KOF Swiss Economic Institute, 2017)
While it is well understood that industrialized countries use aid to grant political favors, little research covers alternative channels such as trade policy towards developing countries. We analyze eligibility investigations and revoking of U.S. Generalized System of Preferences (GSP) benefits to see whether political friends of the U.S. receive favorable treatment. While countries politically aligned with the U.S. are equally likely to be investigated, they are significantly less likely to have their benefits suspended.
Keywords: F13; F53; O19; O24; 330; Development; Trade Policy; United Nations General Assembly